Osteocalcin immunolabeling during the alveolar healing process in ovariectomized rats treated with estrogen or raloxifene - Luvizuto, Eloa Rodrigues [UNESP] (2010)
The influence of an estrogen-deficient state was evaluated in this study and also its treatments with estrogen (E(2)) or with raloxifene (RLX) on the expression of osteocalcin during the periods of the chronology of the alveolar bone healing process (7, 14, 21, 28 and 42 post-extraction days) by means of immunohistochemistry reactions and histomorphometric analysis. Rats (200-220 g) with oestrus cycles normal were either OVX or sham-operated and divided into four groups: sham, OVX control (OVX/O), estrogen (OVX/E(2); 17 beta-estradiol, 400 mu g/mo) and raloxifene (OVX/RLX; 1 mg/kg bw/d) groups. Histomorphometric analysis showed the sham group presented the highest mean value of bone formation post-extraction. The reaction of immunohistochemistry for osteocalcin presented stronger expression of osteocalcin with predominance at 14 and 21 days on sham group. The OVX/RLX group presented better results than OVX/E2, considering the expression of osteocalcin in osteoblastic lineage cells, but still inferior than the sham group. It was concluded that ovariectomy decreases the mineralization process and the osteocalcin expression during the chronology of the alveolar healing process that is not totally recovered with estrogen replacement or raloxifene treatment. (C) 2009 Elsevier B.V. All rights reserved.